Probable prostate cancer in a pre-Incaic individual from Pukara de la Cueva, northwestern Argentina - Luna, Leandro Hernan (2015)
Prostate carcinoma is a common malignant neoplasia that mostly metastasizes to bone in males. Nonetheless, the number of paleopathological cases reported is very small. Most of them were identified in Europe, and only two came from South American individuals. The purpose of this paper is to document the lesions identified in a pre-Columbian (around 1400 AD) individual that corresponds to a middle adult male from Pukara de la Cueva, Jujuy province, in the Northwest region of Argentina. The skeleton was found disarticulated but it is nearly complete and well preserved. The general character of the lesions observed is predominantly proliferative in nature, but osteolytic and mixed patterns were also detected in both axial and appendicular skeleton. Macroscopically, this overall pattern and the distribution of the lesions are compatible with a secondary cancer. Radiological examination showed multiple dense and irregular areas in several bones. The lesions visible by external inspection and by radiographs are in concordance with changes which are documented to occur in the course of prostatic carcinoma. The exuberance and dissemination of the lesions all over the skeleton led infer individual cachexy implying that he would have been assisted by his family and/or social group during the chronic process. Different carcinogenic risk factors associated to this kind of disease are discussed. This analysis adds new evidence of pre- Columbian carcinoma in South American native populations, as knowledge from clinical cases is considered to delineate a differential diagnosis.